TINJAUAN YURIDIS STANDAR MUTU PRODUK DAN PERAN BPOM DALAM MENCIPTAKAN IKLIM PERLINDUNGAN KONSUMEN YANG BAIK DI INDONESIA - Trinah Asi Islami (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2019)
Business has become a routine that has the highest percentage of interest to the public at this time. This digitalization era is one of the facilities to facilitate businesses in running their businesses. However, the facility does not rule out the possibility for business actors to cheat in their business, bearing in mind the objective of the business is to seek maximum profits. The purpose of business by obtaining the maximum profit is permitted, but business actors continue to do business in a fair manner and the products produced are prohibited from harming consumers and the most important thing is that businesses can apply product quality standards that are legalized by BPOM. However, business operators are often found intentionally circulating their products, especially drugs, food and beverage products, and cosmetics that do not yet have a BPOM permit. The fraudulent behavior of the business actor must be immediately stopped with discipline and tightening regarding the regulation of product quality standards. The purpose of this research, specifically to find and understand product quality standards that are applied in Indonesia and the role of BPOM as a drug and food control agency to create a climate of good consumer protection in Indonesia. In general, to deepen science, especially in law of consumer protection. The research of method is the normative juridical method. The discussion in this research is related to regulation the standards of product quality that must be applied by businesses and the role of BPOM in efforts to create a good consumer protection climate in the Indonesia. The conclusions of this research include that to affixing of SNI to products and supervision in the Department of Industry and Trade in category of export commodities must not be lower than SNI while for imported commodities the SNI and the role of BPOM as regulators and filters in the supervision of drug and food products in Indonesia are applied. Keywords: SNI Quality Standards, Products, BPOM and Consumer Protection Law